Special considerations for women with hidradenitis suppurativa - Collier, Erin (Int J Womens Dermatol, 2020)
Hidradenitis suppurativa (HS) is a chronic, debilitating disease that manifests as painful nodules, abscesses, sinus tracts, and scars with a predilection for intertriginous sites. HS disproportionately affects women of childbearing age and often leads to impairments in patients’ health-related quality of life. Women with HS face unique challenges related to menstruation, pregnancy, and lactation that require additional strategies for optimization of management. Practical interventions include lifestyle modifications, treatment of premenstrual HS flares, enhancing HS management during pregnancy, and creating optimal delivery plans in collaboration with obstetricians. This discussion is based on expert recommendations and aims to highlight the special challenges for women with HS, as well as provide a practical discourse on optimizing care of female patients with HS.